2017
DOI: 10.2196/mhealth.6522
|View full text |Cite|
|
Sign up to set email alerts
|

Mobile App-Based Interventions to Support Diabetes Self-Management: A Systematic Review of Randomized Controlled Trials to Identify Functions Associated with Glycemic Efficacy

Abstract: BackgroundMobile health apps for diabetes self-management have different functions. However, the efficacy and safety of each function are not well studied, and no classification is available for these functions.ObjectiveThe aims of this study were to (1) develop and validate a taxonomy of apps for diabetes self-management, (2) investigate the glycemic efficacy of mobile app-based interventions among adults with diabetes in a systematic review of randomized controlled trials (RCTs), and (3) explore the contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
223
0
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(261 citation statements)
references
References 46 publications
11
223
0
10
Order By: Relevance
“…There is growing evidence on the impact of mHealth interventions for the management of diabetes [23,32]. Given the many different mHealth tools, the most effective method and setting for the management of GDM are still under discussion [33].…”
Section: Discussion Principal Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence on the impact of mHealth interventions for the management of diabetes [23,32]. Given the many different mHealth tools, the most effective method and setting for the management of GDM are still under discussion [33].…”
Section: Discussion Principal Resultsmentioning
confidence: 99%
“…mHealth technologies can potentially serve as a new tool for managing disease and promoting healthy behaviour [20]. There is increasing evidence that mHealth interventions help patients to control their blood sugar levels [21][22][23] and elicit patient engagement [24]. However, two systematic reviews on health professionals' acceptance found divergent results [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Participants from Queensland, Australia were recruited Eligibility criteria were: females aged 18+, who resided in Queensland, Australia, and had at least one child aged [5][6][7][8][9][10][11][12] months at enrolment. Ownership of a smartphone was required for intervention delivery.…”
Section: Study Settingmentioning
confidence: 99%
“…Increasingly, apps are being used by health agencies and researchers to gather and present information to study participants and the general public. There is a growing body of evidence showing the successful use of smartphone apps to encourage healthy habits such as increasing physical activity [3] and promoting weight loss [4], managing chronic disease [5,6], and delivering mental health programs [7]. One area that…”
Section: Introductionmentioning
confidence: 99%
“…These mHealth interventions have been applied to monitoring postoperative care [2,3], diabetes self-management [4,5], smoking cessation [6,7], care and prevention of HIV and other sexually transmitted diseases [8], and more. As these interventions begin to spread throughout healthcare, there has been a growing interest in the response to these applications, including topics such as acceptability and feasibility [2], satisfaction by patients and providers [5], and efficiency [4]. However, there is limited research measuring users' comfort in operating smartphone functions, and whether comfort increases as a result of engagement with these applications.…”
Section: Introductionmentioning
confidence: 99%